Profiling Heterogeneous Circulating Tumor Cells (CTC) Populations in Pancreatic Cancer Using a Serial Microfluidic CTC Carpet Chip. Issue 12 (26th September 2018) - Zeinali, Mina; Murlidhar, Vasudha; Fouladdel, Shamileh; Shao, Shimeng; Zhao, Lili; Cameron, Heather; Bankhead, Armand; Shi, Jiaqi; Cuneo, Kyle C.; Sahai, Vaibhav; Azizi, Ebrahim; Wicha, Max S.; et al.
Abstract: Although isolation of circulating tumor cells (CTCs) from pancreatic adenocarcinoma patients is feasible, investigating their clinical utility has proven less successful than other cancers due to the limitations of epithelial cellular adhesion molecule (EpCAM)‐only based CTC assays. An integrated technology‐ and biology‐based approach using a microfluidic "Carpet Chip" is presented to study the biological relevance of heterogeneous CTC populations. Both epithelial CTCs (EpCs) and epithelial‐to‐mesenchymal transition (EMT)‐like CTCs (EMTCs) are isolated simultaneously from the whole blood of pancreatic cancer (PaCa) patients ( n = 35) by separately targeting two surface markers: EpCAM and CD133. Recovery of cancer cell lines spiked into whole blood is ≥97% with >76% purity. Thirty‐four patients had ≥5 EpCs mL −1 and 35 patients had ≥15 EMTCs mL −1 . Overall, significantly higher numbers of EMTCs than EpCs are recovered, reflecting the aggressive nature of PaCa. Furthermore, higher numbers of EMTCs are observed in patients with lymph node involvement compared to patients without. Gene expression profiling of CTCs from 17 patients reveals that CXCR1 is significantly upregulated in EpCs, while known stem cell markers POU5F1/Oct‐4 and MYC are upregulated in EMTCs. In conclusion, successful isolation and genomic profiling of heterogeneous CTC populations are demonstrated, revealing genetic signatures relevant to patient outcomes. Abstract : "Carpet Chip" uses sequential immunoaffinity‐based microfluidics to study the biological relevance of heterogeneous circulating tumor cell (CTCs). Both epithelial (EpCs) and epithelial‐to‐mesenchymal transition (EMT)‐like CTCs (EMTCs) are detectable from the blood of pancreatic cancer patients. Based on our observations of EMTCs and patient lymph node involvement, individualizing therapies targeting genes involved in EMT could reduce metastasis, thereby improving patient survival.